Formulation of Solid Body Wash From Dragon Fruit Peel Waste With Pandan Leaf Extract - Siswanto, Anggun Puspitarini; Aldo, Georgius (UI Scholars Hub, 2003)
This paper highlights the formulation of dragon fruit waste material for a solid body wash, which arguably contain better substance for skin health. The result of this experiment opens up a possibility to be applied as part of community project, contributing to sustainable environment and healthier lifestyle. Red dragon fruit (Hylocereus polyrhizus) is a plant originating from a dry tropical climate with a fairly thick peel that accounts for 30%–35% of the fruit’s total weight. The peel is rarely used or reprocessed and thus often becomes waste. The peel’s polyphenol and other important substances component makes it rich in antioxidants. Owing to these contents, dragon fruit peel is a suitable ingredient for making bath bar soap. In this study, pandan leaf extract was used as an additive as its contents help increase antioxidant levels in solid body wash. This study aimed to determine the best bar soap formulation using dragon fruit peel and pandan leaf extract and the most effective method (FTC versus DPPH), as well as moisture content and pH levels analysis. Results showed that the samples with dragon fruit peels have the highest moisture content, pH, and antioxidant activity. In conclusion, dragon fruit peel can be reused as a supporting ingredient in bar soap. Dragon fruit peel and pandan leaf extract are highly effective for increasing the antioxidant activity and consequently improve the quality of solid body wash.